Exploring the impact of co-fermentation Saccharomyces cerevisiae and Lactobacillus sp. on stingless bee-honey cider fermentation - Thipraksa, Junjira; Michu, Panisa; Kongthong, Alisa; Chaijak, Pimprapa (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
Stingless bee honey is a nutritious food that contains a variety of vitamins, minerals, enzymes, and antioxidants. It is known to have higher nutritional and medicinal properties compared to honey produced by other bee species. Cider is a well-known functional drink that contains high antioxidants, which can help protect against cellular damage caused by free radicals. This study aimed to investigate the potential of co-fermentation with yeast (Saccharomyces cerevisiae) and bacterium (Lactobacillus sp.) in producing high-antioxidant honey cider when compare with standard antioxidant. The results showed that honey cider co-fermented with both microorganisms for 14 days had significantly higher antioxidant activity (145.27 ± 0.20 µg TE/mL) compared to single culture fermentation (p < 0.05). Gas chromatography-mass spectrometry (GC-MS) analysis revealed the presence of several bioactive compounds in the stingless bee honey cider. These compounds include methylenecyclopropanecarboxylic acid, 2(5H)-furanone, 2-methylbicyclo[4.3.0]non-1(6)-ene, bicyclo[3.1.0]hex-2-ene, 4-methyl-1-(1-methylethyl), D-limonene, benzene, 1-(1-butenyl)-4-methoxy, and phytol. These compounds possess various beneficial activities, such as antioxidant, anti-inflammatory, antimicrobial, and anticancer properties. The identification of these compounds in the stingless bee honey cider suggests that it may have potential health benefits beyond its nutritional value. The co-fermentation approach using S. cerevisiae and Lactobacillus sp. could be considered a promising strategy for developing antioxidant-enriched honey cider with potential health benefits.